Integration of accounting information systems and reporting into the digital model of institutional financial management - Shyshkova, N.; Shyshkov, S. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
This article examines the integration of accounting and financial reporting information systems into a unified digital financial management model. In the context of digital transformation, such integration has strategic significance for ensuring the efficiency and resilience of enterprises and serves as an essential component of the institutional environment necessary for integration with international markets, particularly the EU. The study generalizes current scientific trends related to integrating accounting and reporting information systems into a digital financial management model in order to strengthen the linkages among accounting, analysis, and strategic planning within a single digital framework. This integration enhances the efficiency and transparency of managerial processes. Particular attention is devoted to the technological, organizational, methodological, and human-resource dimensions of integration, as well as to the necessity of a systematic approach, phased implementation, and alignment with the enterprise’s strategic development goals. The key advantages of integrating information systems are identified, including improved financial management quality, greater operational efficiency, analytical transparency, and better-substantiated managerial decisions. The results of integration are shown to be comprehensive: they enhance the operational, analytical, managerial, and economic components of the enterprise’s activities and create the preconditions for strengthening financial stability and competitiveness. The article outlines the requirements for the architecture of an integrated digital financial model and the principles of its formation, emphasizing its capacity to ensure coherence, transparency, flexibility, and resilience in financial management amid digital and institutional transformation. The main stages and components of integrating accounting information systems into a digital financial management model are proposed, with attention to the key actions of an individual enterprise and the advantages of developing a digital financial ecosystem. The integration of accounting and financial reporting information systems is not only a tool for optimizing management processes but also a strategic direction of digital and institutional transformation. It supports sustainable development, increases competitiveness, and enables enterprises to adapt to the demands of the digital economy.